(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article explores the shift in epistemology from traditional truth-conditional logic to a cognitive linguistic framework. It posits that human knowledge is not an abstract entity but a conceptually structured domain derived from embodied experience. Central to this is the work of Lakoff and Johnson, who argue that metaphors are fundamental cognitive mechanisms rather than mere rhetorical flourishes. Moreover, article tries to mapping the process of learning onto physical movement toward a destination, complete with obstacles and crossroads as well as conceptualizing ideas as objects that can be "grasped," "acquired," or "stored."